Changes in business and management structures of large Singapore firms - Lim, Sihui (2008)
The main aim of this project is to find out how GLCs and Private companies differ in 4 areas before and after the Asian Financial Crisis. These 4 areas are: divestment of non-core assets, geographical diversification of subsidiaries, change in CEO and Chairman and lastly the change in shareholding.